Multiple normolipemic tendinous xanthoma in coexistence with bilateral terminal glaucoma and syndactyly - Cevallos-Riva, Liz Karen (2021)
Tendinous xanthomas are usually associated with hyperlipidemia, normolipemic tendinous xanthomas are uncommon. The histopathology of this condition is characterized by the presence of foam cells, cholesterol clefts, and Touton cells. We present a 22-year-old male patient with normolipemic tendon xanthomas, coexisting with bilateral terminal glaucoma and syndactyly, where histology and immunohistochemistry were very useful to reach the definitive diagnosis.